Tradition of Petang Megang and Its Influence in Changing The Siak Riverside in Pekanbaru - Fatma, Destia Raudha; Lukito, Yulia (CSID Journal of Infrastructure Development, 2021)
Siak River is the main river in the capital city of Riau Province, and it plays a vital role in the history and the development of the city of Pekanbaru. People use the river as the source of water, transportation, and even the traditional ceremony of Petang Megang, which indicates the close connection of Pekanbaru people with the river. The Siak riverside is the center of the city, with the old town, markets, settlements, and the royal house located near the river. The community's attachment to the river can be seen through Petang Megang, which is known as a tradition to clean and purify the body and soul to welcome the holy month of Ramadan. During Petang Megang, many people go to the river, perform mandi balimau and even hold competitions and festivals that attract tourists. This paper discusses how Petang Megang reflects the connection of local people to the river and influences the spatial form of the Siak riverside. The findings show that since there are some changes in the practice of Petang Megang, such as boat competition and music festivals, the government develops the Siak riverside not only to accommodate Petang Megang but also to attract tourists. Unfortunately, the development limit access of local people to the river.